PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA ONLINE SHOP SHOPEE KHAGI BABY DI BOGOR - Sayni, Yayu; Sudarsono, Agus (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of Price and Promotion on Purchasing Decisions at Online shop Shopee Khagi Baby in Bogor. The research method used is associative quantitative method. The sampling technique used in this study was 98 respondents. Data analysis techniques with instrument tests, namely validity tests and reliability tests, classical assumption tests, namely normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, simple linear regression tests, multiple linear regression tests, correlation coefficient tests, determination coefficient tests and hypothesis tests, namely t tests and f tests. The result of this study is that price has a significant effect on purchasing decisions with the hypothesis test obtained tcount > ttable (8.195> 1.985). Promotion has a significant effect on purchasing decisions with the hypothesis test obtained tcount > ttable (5.880> 1.985). Price and Promotion simultaneously have a significant effect on purchasing decisions with the hypothesis test obtained fcount > ftabel (33.290> 3.092). Thus, it can be concluded that price and promotion have a positive and significant effect on purchasing decisions at the Shopee Khagi Baby online shop. The coefficient of determination has an effect or contributes to a simultaneous influence of 0.400 or 40.0%, the remaining 60.0% is influenced by other factors .